2002
DOI: 10.1080/003655202761020579
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 Gene Polymorphisms in Dutch and Chinese Patients with Inflammatory Bowel Disease

Abstract: C-318T and A+49G CTLA4 gene polymorphisms and their haplotypes are not associated in Dutch Caucasian patients with IBD and in Chinese patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
2
43
3
Order By: Relevance
“…Nevertheless, our study was underpowered to detect smaller effects such as an OR of 1.14 associated with type 1 diabetes [13]. Interestingly, our data are in accordance with those obtained in a study of IBD in a Dutch Caucasian population in which no association between ϩ49A/G and C-318T CTLA4 polymorphisms and IBD was observed [22]. These findings and our results suggest that CTLA4 polymorphism does not play a major role in IBD susceptibility.…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, our study was underpowered to detect smaller effects such as an OR of 1.14 associated with type 1 diabetes [13]. Interestingly, our data are in accordance with those obtained in a study of IBD in a Dutch Caucasian population in which no association between ϩ49A/G and C-318T CTLA4 polymorphisms and IBD was observed [22]. These findings and our results suggest that CTLA4 polymorphism does not play a major role in IBD susceptibility.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, IL-2-deficient T cells have reduced CTLA-4 expression but increased production of RANKL, and these two defects seem responsible for lymphoaccumulation and AHA, or osteopenia and IBD, respectively. Consistent with the lack of correlation between reduced CTLA-4 expression and IBD, CTLA-4-deficient mice do not develop IBD (M.-L. Alegre, unpublished observation; data not shown), and CTLA-4 polymorphisms have not been associated with IBD in humans (40).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, a study from Oxford compared 645 CD patients with 1190 controls and showed an association of ATG16L1 with CD [14] . To understand fully the function of this gene, a study utilized oligo-based silencing RNA directed against ATG16L1 isoforms, where autophagy was induced by Salmonella typhimurium in ATG16L1 knockdown HEK293 cells.…”
Section: Autophagy-related 16-like 1 Protein Complexmentioning
confidence: 98%